2022
DOI: 10.3389/fpls.2022.882120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolome and Functional Properties of Three Korean Cucumber Cultivars

Abstract: Cucumber (Cucumis sativus L.) is consumed worldwide and various cultivars have been developed to enhance fruit quality. However, few studies have comprehensively evaluated the quality of various cultivars. We carried out a metabolomics approach to study the three different cucumber cultivars (Chuichung, White Dadagi, and Mini) and their parts (peel and flesh) coupled with antioxidant activities. The amino acids, sugars, flavonoids, carotenoids, and chlorophylls were upregulated in Mini flesh; however, in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Cucumber peel has high amounts of chlorophylls, which have a crucial effect on fruit color and taste [39,40]. Glycine, serine and sugar derivatives in the peel determine fruit sweetness [41]. The results of our study confirmed that, in a low-density canopy, the higher the cucumber fruit leaf chlorophyll content, the higher the sugar content and the better the fruit taste (Figure 7).…”
Section: Discussionsupporting
confidence: 71%
“…Cucumber peel has high amounts of chlorophylls, which have a crucial effect on fruit color and taste [39,40]. Glycine, serine and sugar derivatives in the peel determine fruit sweetness [41]. The results of our study confirmed that, in a low-density canopy, the higher the cucumber fruit leaf chlorophyll content, the higher the sugar content and the better the fruit taste (Figure 7).…”
Section: Discussionsupporting
confidence: 71%
“…After extraction, the fiber was removed from the holder and desorbed at the GC port for 1 min at 270°C. The analytical methods and operational parameters used for VOC analysis were based on our previous study ( Jo et al., 2022 ). Sample analysis was performed using two analytical replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 1 , isovitexin 2′′-(6′′′-(E)-feruloylglucoside) 4′-glucoside, was first isolated and structurally characterized from the leaves of Cucumis sativus [ 43 ]. Compound 4 , saponarin 4′-O-glucoside, was initially discovered in a flowering herb of Lagenaria siceraria [ 44 ], but Cucumis sativus is now the primary known source of this compound [ 45 ]. Interestingly, both compounds 1 and 4 are apigenin glycosides, with isovitexin (apigenin 6-C-glucoside) serving as the precursor for the biosynthesis of saponarin (apigenin 6-C-glucoside-7-O-glucoside) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%